2021
DOI: 10.1093/fampra/cmab159
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of non-opioid interventions to reduce opioid withdrawal symptoms in patients with chronic pain: a systematic review

Abstract: Background Dealing with the opioid crisis, medical doctors are keen to learn how to best treat opioid dependency in patients with chronic non-cancer pain. Opioid replacement therapy is commonly used, but success rates vary widely. Since many patients still experience severe withdrawal symptoms, additional interventions are necessary. Objective To review the effectiveness of interventions in the treatment of withdrawal symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“… 10 Remarkably, the systematic review of controlled trials of interventions for opioid withdrawal during opioid tapering, found only 1 study meeting inclusion criteria. 11 This study found no between group differences in opioid withdrawal symptoms between varenicline vs placebo. There is a great need to develop improved strategies for treating withdrawal in opioid tapering.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“… 10 Remarkably, the systematic review of controlled trials of interventions for opioid withdrawal during opioid tapering, found only 1 study meeting inclusion criteria. 11 This study found no between group differences in opioid withdrawal symptoms between varenicline vs placebo. There is a great need to develop improved strategies for treating withdrawal in opioid tapering.…”
mentioning
confidence: 52%
“…Managing opioid withdrawal was investigated by Quattlebaum et al’s 10 case study and Langejan et al’s 11 systematic review. The case study reports the use of rapid administration of high-dose buprenorphine for buprenorphine precipitated withdrawal in a patient who did not respond to recommended dose escalation.…”
mentioning
confidence: 99%
“…Klinik deneyimler, BNK'nın azaltılmaya başlaması ile ortaya çıkabilen özellikle ağrı gibi belirtilerin iyi yönetilemediği durumlarda tedaviyi yarıda bırakma ve tekrar kullanmaya başlama durumlarının sık yaşandığını göstermektedir. Bununla birlikte literatürde özellikle bu süreçte ortaya çıkan belirtileri azaltan müdahalelere ilişkin klinik çalışmalardan elde edilen kanıtların yeterli olmadığı, terapötik seçeneklere yoğun bir ihtiyaç duyulduğu bildirilmektedir (32).…”
Section: Klinikte Ağrıya Optimal Yaklaşımın öNündeki Engeller Ve öNer...unclassified
“…Lack of alternative treatment for CNCP and the perception of infrequent adverse events have contributed to the continuing opioid crisis 11 20. Moreover, prescribers may be reluctant to deprescribe, particularly if there is limited access to effective pain management treatments 21 22.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are taking high doses for long periods demonstrate high psychological distress and low self-efficacy,33 34 highlighting the importance of working with the patient for behaviour change and pain acceptance. Opioid tapering has found improvements in pain response and pain tolerance, without a decline in function or quality of life,20 while a recent systematic review showed high patient interest in support for tapering 32. GP supervised tapering and Multidisciplinary Team (MDT) group therapeutic sessions are advocated to reduce long-term opioid use 35–37…”
Section: Introductionmentioning
confidence: 99%